THE EVOLUTION OF MOBILE MARKETING - S. Raufjonov (Web of Journals Publishing, 2023)
This article examines the transformative journey of mobile marketing in the digital age, tracing its evolution from its inception to its current state as a dominant force in modern advertising strategies. By analyzing technological advancements, consumer behaviors, and industry trends, this study sheds light on the dynamic landscape of mobile marketing. The article underscores the pivotal role of mobile devices in shaping consumer interactions and explores how businesses have adapted their approaches to engage and convert audiences effectively. Through a blend of historical analysis and contemporary case studies, this research contributes to a comprehensive understanding of mobile marketing's trajectory and its implications for future marketing endeavors.
Keywords: Mobile marketing, evolution, digital age, consumer behavior, technological advancements.